Efforts to Increase Mathematical Logical Intelligence Through Development of Student Worksheets Based on Problem Based Learning (Universitas Negeri Semarang, 2020)
Chemistry is a subject that is closely related to learning that requires students to be active in problem solving. Because of this, a worksheet development is needed to support chemistry learning activities. This study aims to develop a Student Based Worksheet (LKPD) based on Problem Based Learning (PBL) hydrolysis material to improve mathematical logical intelligence. The quality of LKPD is measured by the criteria of validity, effectiveness, and practicality in the learning process. The development model used in this study is a 3D model (define, design and develop). Data analysis techniques using qualitative and quantitative tests. The product development validation was carried out by the validator of media experts and material experts, while the trial was conducted by 36 students of class XI IPA 5. The results of the validator analysis stated that the quality of learning material was included in the excellent category with a percentage of 93.77% of the material experts and 94.46% of media experts. The effectiveness of LKPD indicated an increase in mathematical logical intelligence of students with the achievement of N-gain of 0.56 in the medium category and classical completeness of 86.11%. Student responses to the practicality of using LKPD showed results of 77.78% which included in the very good category and 22.22% included in the good category. Based on the results obtained, it can be concluded that LKPD fulfills valid, effective, practical criteria, and can improve mathematical logical intelligence.